The self-association of HMGB1 and its possible role in the binding to DNA and cell membrane receptors - Anggayasti, Wresti Listu; Mancera, Ricardo; Bottomley, Steven; Helmerhorst, Erik (Elsevier, 2017)
© 2016 Federation of European Biochemical SocietiesHigh mobility group box 1 (HMGB1), a chromatin protein, interacts with DNA and controls gene expression. However, when HMGB1 is released from apoptotic or damaged cells, it triggers proinflammatory reactions by interacting with various receptors, mainly receptor for advanced glycation end-products (RAGE) and toll-like receptors (TLRs). The self-association of HMGB1 has been found to be crucial for its DNA-related biological functions. It is influenced by several factors, such as ionic strength, pH, specific divalent metal cations, redox environment and acetylation. This self-association may also play a role in the interaction with RAGE and TLRs and the concomitant inflammatory responses. Future studies should address the potential role of HMGB1 self-association on its interactions with DNA, RAGE and TLRs, as well as the influence of physicochemical factors in different cellular environments on these interactions.